valuasi ekonomi Valuasi Ekonomi Sumber Daya Kelautan dan Perikanan di Pulau Tikus Kota Bengkulu - Zamdial, Zamdial; Hartono, Dede; Syahputra, Octianto (Journal of Tropical Marine Science, 2023)
Tikus Island is surrounded by a coral reef so that it is able to protect the island from abrasion due to large waves. The coastal and marine resources of Tikus Island have various ecological and economic functions. The purpose of this study is to calculate and analyze the total benefit value of potential marine and fisheries resources in the Tikus Island Area, Malabro Village, Teluk Segara District, Bengkulu City. This research was conducted in March - April 2022. This study used a comprehensive survey method. Sampling using Purposive Sampling technique. Respondents value the benefits of existence consist of the level of education, namely with the Axidental Sampling technique. The results of this study obtained the total benefit value of marine and fisheries resources on Tikus Island is Rp. 19.205.799.426,-/year with a direct use value of Rp. 2.455.820.000,-/year, inderect use value of Rp.989.047.590 ,-/year, option value of Rp. 681.424.836,-/year, excitence value of Rp. 14.833.925.000,-/ year, bequest value Rp. 245.582.000,-/year Keywords : Economic Valuation, Tikus Island, Direct Use Value, Indirect Use Value, Total Economic Value